Eksplorasi Penggunaan Artificial Intelligence dalam Menemukan Preferensi Fasad Hijau - Devita Anggreani; Wendy Sunarya (Universitas Medan Area, 2026)
Digital technology continues to develop and is involved in all aspects of human life, including architecture). Initially, the transformation of digital architecture was limited to computerization to accelerate drawing, but it has now expanded to statistical computation such as data science and artificial intelligence, allowing technology to play a role in the conceptualization process .AI (Artificial Intelligence), as a product of data science, began to emerge in architecture through the trend of rendering and image generation using prompts. AI is claimed to assist architects, designers, and students in creating architectural works, in exploring designs more quickly, and in supporting brainstorming and the development of design styles. AI platforms, particularly text-to-image generative models, hold great potential in creative work. Generative design can produce various design alternatives automatically based on predetermined criteria, enabling architects to explore design visualizations more efficiently. However, AI is only optimal when there is alignment between input and output perceptions, namely between the planner’s ideas and the data contained within the AI system. This study focuses on comparing the alignment of perceptions between AI and future planners (architecture students) to examine the extent to which AI can realize design visualizations and meet user expectations.